Role Ambiguity on Job Satisfaction with Job Stress as a Mediating Variable - Putra, Muhamad Farid; Andriani, Chichi (Human Resource Management Studies, 2024)
This study aims to analyze: (1) The effect of role ambiguity on job satisfaction (2) the effect of role ambiguity on job stress (3) the effect of job stress on job satisfaction (4) the effect of role ambiguity on job satisfaction with job stress as a mediating variable in Batuhampar health center employees. This research is quantitative in nature. The population in this study were employees of the Batuhampar health center with a total of 36 people. The sampling technique used a total sample with a total of 36 employees. Data collection using a questionnaire with a Likert scale. Data analysis techniques used through smart PLS 4 software. The results of data processing in this study show that: (1) role ambiguity has a negative and significant effect on job satisfaction of Batuhampar health center employees (2) role ambiguity has a positive and significant effect on job stress (3) job stress has a negative and significant effect on job satisfaction (4) job stress negatively and significantly mediates the effect of role ambiguity on job satisfaction of Batuhampar health center employees.